2020
DOI: 10.3390/agronomy10121885
|View full text |Cite
|
Sign up to set email alerts
|

A First Investigation of Agriculture Sector Perspectives on the Opportunities and Barriers for Agrivoltaics

Abstract: Agrivoltaic systems are a strategic and innovative approach to combine solar photovoltaic (PV)-based renewable energy generation with agricultural production. Recognizing the fundamental importance of farmer adoption in the successful diffusion of the agrivoltaic innovation, this study investigates agriculture sector experts’ perceptions on the opportunities and barriers to dual land-use systems. Using in-depth, semistructured interviews, this study conducts a first study to identify challenges to farmer adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 43 publications
0
61
0
Order By: Relevance
“…Given that agrivoltaics are a relatively nascent form of solar development, there is a dearth of social science research dedicated to investigating the social acceptability and perceptions of the technology. Existing research concerned with the social dimensions of agrivoltaic development suggests that community acceptance, farmer adoption, and local regulatory environments will play a crucial role in the broader realization of these systems (Ketzer et al, 2019;Pascaris, 2021;Pascaris et al, 2020Pascaris et al, , 2021bLi et al, 2021). Based on previous theoretical and empirical studies related to social acceptance of renewable energy (RE) (e.g., Walker, 1995;van der Horst, 2007;Ansolabehere & Konisky, 2009;Sovacool, 2009;Batel et al, 2013;Fast, 2013), it is anticipated that successful deployment of agrivoltaics will necessitate sensitivity to and accommodation of public perceptions, especially rural perceptions, related to solar infrastructure on farmland.…”
Section: Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that agrivoltaics are a relatively nascent form of solar development, there is a dearth of social science research dedicated to investigating the social acceptability and perceptions of the technology. Existing research concerned with the social dimensions of agrivoltaic development suggests that community acceptance, farmer adoption, and local regulatory environments will play a crucial role in the broader realization of these systems (Ketzer et al, 2019;Pascaris, 2021;Pascaris et al, 2020Pascaris et al, , 2021bLi et al, 2021). Based on previous theoretical and empirical studies related to social acceptance of renewable energy (RE) (e.g., Walker, 1995;van der Horst, 2007;Ansolabehere & Konisky, 2009;Sovacool, 2009;Batel et al, 2013;Fast, 2013), it is anticipated that successful deployment of agrivoltaics will necessitate sensitivity to and accommodation of public perceptions, especially rural perceptions, related to solar infrastructure on farmland.…”
Section: Previous Researchmentioning
confidence: 99%
“…Further, proactively avoiding threat to local interests and priorities was identified as extremely important among respondents when planning for agrivoltaic projects; this highlights the importance of including the public in the planning process to meaningfully incorporate existing agricultural practices in system design and to ensure that the project represents the interests and identity of the host community. Addressing concerns about unfair distribution of project benefits could include the establishment of contracts between solar developers and farmers that are accessible to the public and outline costs and compensation for both parties (Pascaris et al, 2020).…”
Section: Policy Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a recent study showed, long term land productivity and market certainty are often seen as the main arguments favoring the implementation of AV from farmers' perspective [15]. This emphasizes the need for agricultural field trials.…”
Section: Introductionmentioning
confidence: 99%